Liquid Biopsy in Small Cell Lung Cancer—A Route to Improved Clinical Care? - Matt Church; Louise Carter; Fiona Blackhall (Cells, 2020)
Small cell lung cancer (SCLC) has a particularly poor prognosis despite the high initial response to first-line systemic therapy, and there is a well-recognised lack of meaningful treatments beyond the second line. A number of reasons have been put forward to explain this, including a lack of common, easily-druggable genetic mutations in SCLC and rarity of high-quality tissue samples due to late presentation. Liquid biopsies, including circulating tumour cells (CTCs) and circulating tumour DNA (ctDNA) are increasingly used as surrogates for tumour tissue and have the advantage of being easily obtained serially to inform on the biology of disease progression and acquired chemoresistance, and may provide a pathway to improve care in this notoriously refractory disease. Here we discuss the current evidence behind these liquid biopsy methods in SCLC, and how they could be employed in future clinical care.